The place of trainings in psychological support of personal transformations of police officers (Law and Safety, 2018)
The necessity of the development and implementation of trainings in the framework of psychological support of personal transformations of future law enforcement officers for the optimization of their professional and personal development in the process of professional self-actuating has been substantiated.The author convinces that the essential factor of prevention of personal and professional crises of law enforcement officers is the formed professional identity, which is an integral part of their professional formation. The development of the value sphere of the personality of law enforcement officers helps to optimize their behavior and self-actuating in such spheres of life as occupation, family life, relationships, hobbies. The motivational component is one of the basic in the system of moral regulation of the activities and behavior of professionals and provides a positive attitude to the chosen kind of professional activity, the desire for self-actuating and achievements, moral and professional settings and interests. Motivation acts as a connecting link between true goals, ideals, beliefs of the personality of a cadet and actions, deeds, decisions that he takes.The psychological support is considered by the author as an integral process of diagnosis, prevention and correction of personal transformations of future law enforcement officers in the process of vocational training, which is carried out in all spheres of their activity in higher educational institutions with specific learning conditions. Trainings as a practice of psychological influence are based on active methods of group work, the use of peculiar forms of learning – knowledge, skills and techniques in the field of communication and future professional activities, diagnosis, prevention and correction.The author has studied the expediency of using training programs for the development of professional identity, the formation of value regulators of behavior and the motivational sphere of future law enforcement officers in higher educational institutions with specific learning conditions that will increase the efficiency of professional activity and self-actuating of police officers in modern conditions.